Mediation of effects of biofiltration on bacterial regrowth, Legionella pneumophila, and the microbial community structure under hot water plumbing conditions. Issue 2 (16th November 2017) - Dai, Dongjuan; Proctor, Caitlin R.; Williams, Krista; Edwards, Marc A.; Pruden, Amy
Abstract : Biofiltration limits total bacterial growth but not Legionella pneumophila in hot water systems modified with various plumbing conditions. Abstract : While limiting organic carbon through biofiltration controls microbial regrowth in drinking water main distribution systems, little is known about its effectiveness for building water plumbing systems. Here we examined regrowth under eight plumbing conditions: pipe material (iron or cross-linked polyethylene (PEX)), corrosion control (magnesium rod, elevated pH), corrosion sediments (Fe(OH)3 ), nitrification (ammonium addition), a combination of magnesium rod/iron pipe/ammonium, and a no-modification control using simulated water heaters (SWHs) fed with biofiltered or unfiltered water and incubated at 32 °C. While biofiltration did effectively limit total bacterial numbers (half-log less), it did not offer protection against Legionella pneumophila . By the end of study (day 448), some conditions acted synergistically with (PEX, ammonium) or independently of (magnesium rod, combination) influent biofiltration to increase L. pneumophila numbers. Illumina sequencing of 16S rRNA genes confirmed the enrichment of phylogenetic groups associated with expected functions ( e.g., ammonium, iron, and hydrogen oxidation) under corresponding plumbing modifications and also revealed that biofiltration had an overarching influence on the microbial community structure in the control, Fe(OH)3, and combination conditions. This study demonstrates that a variety of factors under warm water plumbing conditions can override potential influences of upstream biofiltration on L. pneumophila growth.